In situ ESEM investigation of the initial stages of corrosion phenomena on zinc and magnesium surfaces. Issue 5 (5th October 2012) - Rossi, S.; Fedel, M.; Deflorian, F.
<x xml:space="preserve">Abstract</x> This article investigates the initial stages of corrosion phenomena on zinc and magnesium promoted by chlorine contamination by means of an environmental scanning electron microscope (ESEM). In particular, the corrosion of the substrates was promoted in situ in the ESEM chamber by modifying the relative humidity, thus promoting the condensation of water on the metal surface. The metal surfaces were previously contaminated with sodium chlorides. The corrosion morphologies obtained in the ESEM chamber were compared to the degradation promoted by exposing zinc and magnesium samples in the humidostatic chamber.